PELATIHAN PENGOLAHAN PRODUK RUMPUT LAUT UNTUK MENDUKUNG PENGEMBANGAN NUSA LEMBONGAN SEBAGAI DESTINASI WISATA - IGB.S. Dharma; A.P.W.K. Dewi; I M.S. Darmasetiyawan (Buletin Udayana Mengabdi, 2016)
Nusa Lembongan is an area of cultural and maritime tourism. Livelihood Pattern in Nusa Lembongan isclosely related to marine resources. In order to increase the added value and the sale value, seaweed farmingdevelopment should be followed by the development of processing industry. The training that needs to bedone is the development of seaweed processing technology into a variety of processed seaweed-basedproducts. Interviews conducted with the group leader for seaweed processing in Nusa Lembongan shows theunavailability of seaweed jelly candy. The training process for seaweed jelly candies has been going well.Results showed that participants understand the materials that have been given. The success is shown by thepositive response from the participants; by asking questions and responses related to the process of makingcandy jelly seaweed.